2020
DOI: 10.1308/rcsann.2020.0121
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel coated-balloon (PCB) versus standard plain old balloon (POB) fistuloplasty for failing dialysis access

Abstract: Introduction This study aimed to evaluate the safety and efficacy of paclitaxel-coated balloon compared with conventional plain balloon for the treatment of failing native dialysis access. Materials and methods This prospective study included 60 patients presenting to the Kasr Alainy Hospitals and Aseer Central Hospital in the period from September 2015 to December 2017 with failing native vascular access. Dilatation with a plain balloon was done in 30 patients (group I) and with a paclitaxel-coated balloon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The resultant 49 studies were further screened by full‐text assessment to remove publications without full text (n=27), retrospective studies (n=1), and studies without primary outcomes of interest reported (n=2), yielding 19 studies based on 18 unique RCTs. 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A total of 877 and 875 patients in the DCB and PBA groups, respectively, were included in the present meta‐analysis (Table 1 ). These studies were conducted in the United States, Korea, China, Egypt, Spain, Australia, Finland, Singapore, Belgium, Greece, Taiwan, the Netherlands, and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant 49 studies were further screened by full‐text assessment to remove publications without full text (n=27), retrospective studies (n=1), and studies without primary outcomes of interest reported (n=2), yielding 19 studies based on 18 unique RCTs. 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 A total of 877 and 875 patients in the DCB and PBA groups, respectively, were included in the present meta‐analysis (Table 1 ). These studies were conducted in the United States, Korea, China, Egypt, Spain, Australia, Finland, Singapore, Belgium, Greece, Taiwan, the Netherlands, and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy data from two studies that did not report appropriate survival data had to be excluded. 27,33 Finally, no patient level data were available, and thus the subgroup analysis was limited to the results published. It was not possible to perform the planned subgroup analysis of central vein stenosis or recurrent lesions because of the small amount of literature providing the necessary data separately.…”
Section: Discussionmentioning
confidence: 99%
“…Among the retrieved trials, three RCTs were excluded because of insufficient data. RCTs by Karmota 33 and Arabi et al 32 were excluded from the evidence synthesis because of a lack of relevant time to event efficacy data and one year survival data. The RCT by Rai et al 36 was excluded because of limited information to assess its eligibility.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…It has been reported in some small studies that the use of drug-coated balloons (DCB) with a layer of antiproliferative drug paclitaxel may have the potential to improve outcomes. In contrast, other studies reported a contradictory result (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 94%